2023
DOI: 10.3389/fnhum.2023.1126553
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of cognitive impairment in chronic heart failure—A cluster analytic approach

Abstract: BackgroundCognitive impairment is a major comorbidity in patients with chronic heart failure (HF) with a wide range of phenotypes. In this study, we aimed to identify and compare different clusters of cognitive deficits.MethodsThe prospective cohort study “Cognition.Matters-HF” recruited 147 chronic HF patients (aged 64.5 ± 10.8 years; 16.2% female) of any etiology. All patients underwent extensive neuropsychological testing. We performed a hierarchical cluster analysis of the cognitive domains, such as intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Researches have demonstrated that more than 50% of patients with CHF experience secondary brain damage, which can manifest as autonomic damage, cognitive dysfunction, and neuropsychological deficits ( 13 ). In addition to their relation to the grey matter structure of the subcortex and brainstem, these varying degrees of brain damage also involve the integrity of cerebral cortical structure ( 14 ). Several scientific studies have examined the structure of the cerebral cortex, and the cortical regions of patients with CHF have been roughly examined using magnetic resonance imaging (MRI) ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researches have demonstrated that more than 50% of patients with CHF experience secondary brain damage, which can manifest as autonomic damage, cognitive dysfunction, and neuropsychological deficits ( 13 ). In addition to their relation to the grey matter structure of the subcortex and brainstem, these varying degrees of brain damage also involve the integrity of cerebral cortical structure ( 14 ). Several scientific studies have examined the structure of the cerebral cortex, and the cortical regions of patients with CHF have been roughly examined using magnetic resonance imaging (MRI) ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%